1,4-Bis[4-(tert-butylsulfanyl)phenyl]buta-1,3-diyne - Edwin Weber; Wilhelm Seichter; Sebastian Förster; Nadine Seidel (Acta Crystallographica Section E, 2012)
The asymmetric unit of the title compound, C24H26S2, consits of one half-molecule, which is located on a center of inversion. The two benzene rings are exactly coplanar while the tert-butyl group is oriented nearly perpendicular to the ring plane [C—S—C—C = −81.14 (11)°].